2024
DOI: 10.1021/acsomega.3c10271
|View full text |Cite
|
Sign up to set email alerts
|

An Insight on Microfluidic Organ-on-a-Chip Models for PM2.5-Induced Pulmonary Complications

Disha Shah,
Bhavarth Dave,
Mehul R. Chorawala
et al.

Abstract: Pulmonary diseases like asthma, chronic obstructive pulmonary disorder, lung fibrosis, and lung cancer pose a significant burden to global human health. Many of these complications arise as a result of exposure to particulate matter (PM), which has been examined in several preclinical and clinical trials for its effect on several respiratory diseases. Particulate matter of size less than 2.5 μm (PM 2.5 ) has been known to inflict unforeseen repercussions, although data from epidemiological studies to back this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 228 publications
0
1
0
Order By: Relevance
“…Multiorgan-on-chip models or even body-on-a-chip models enable the study of multitissue or even systemic diseases. Numerous reports state that 3D cells/tissue culture methods designed for other organs are utilized in 3D cartilage and bone organ-on-chip. , For, instance, compared to 2D monolayers, Rosser’s research finding demonstrated the importance of 3D microfluidic culture, where chondrocytes displayed a higher differentiated cartilage phenotype and an osteoarthritis-like response to inflammation and therapies . Furthermore, Choudhary and co-workers demonstrated that 3D microfluidic ex vivo cultivation of primary osteocytes could aid in the retention of mature osteocytic phenotypes more effectively than those 2D monolayers, which is important for the advancement of osteoarthritis illness. , …”
Section: In Vitro Models Of Rheumatoid Arthritismentioning
confidence: 99%
“…Multiorgan-on-chip models or even body-on-a-chip models enable the study of multitissue or even systemic diseases. Numerous reports state that 3D cells/tissue culture methods designed for other organs are utilized in 3D cartilage and bone organ-on-chip. , For, instance, compared to 2D monolayers, Rosser’s research finding demonstrated the importance of 3D microfluidic culture, where chondrocytes displayed a higher differentiated cartilage phenotype and an osteoarthritis-like response to inflammation and therapies . Furthermore, Choudhary and co-workers demonstrated that 3D microfluidic ex vivo cultivation of primary osteocytes could aid in the retention of mature osteocytic phenotypes more effectively than those 2D monolayers, which is important for the advancement of osteoarthritis illness. , …”
Section: In Vitro Models Of Rheumatoid Arthritismentioning
confidence: 99%